Comparative energy and environmental analysis of different small-scale biomass-fueled CCHP systems. (15th January 2023) - Rajabi Hamedani, Sara; Villarini, Mauro; Marcantonio, Vera; di Matteo, Umberto; Monarca, Danilo; Colantoni, Andrea
Abstract: Biomass combined cooling, heating, and power (CCHP) systems promote energy efficiency and reduce overhead costs in bioenergy production. On the necessity of assessing the sustainability of bioenergy technologies, this study performs a comprehensive life cycle assessment (LCA) of small-scale biomass CCHP technologies regarding technical alternatives. The novelty stems from comparing configurations based on sustainability indicators, the energy payback time, and conflicting objectives (maximizing energy revenues and minimizing environmental costs). Accordingly, four configurations attributed to biomass conversion technologies (organic Rankine cycle (ORC) and gasifier) and cooling units (electric heat pump, absorption chiller) are considered for LCA modeling. The results reveal that the highest share of human health (70–85%), ecosystem quality (50–60%), climate change (60–80%) and resources (70–80%) in all configurations belongs to biomass conversion technologies. In terms of Global warming, impacts related to gasification-ICE-based configurations outweigh ORC-based configurations (30–47%) due to higher auxiliary energy demand in the gasification process. In contrast, the CCHP systems driven by ORC are more reliable in refunding primary energy in the short term, 2.4–2.8 years. As a final result, the gasifier coupled with the electric heat pump is the most optimum configuration due to higher energy profits and lower environmental costs. Highlights: A comparative life cycle assessment of four biomass CCHP configurations. The prime movers are the most effective parameters respect to environmental issues. Gasification-ICE-electric heat pump is favorable regarding sustainability indicators. The fossil-based CCHP doubles overall impacts compared to the bioenergy plant.